Hydrothermal heating with sulphuric acid contributes to improved fermentative hydrogen and methane co-generation from Dianchi Lake algal bloom. (15th July 2019) - Cheng, Jun; Yue, Liangchen; Hua, Junjie; Dong, Haiquan; Li, Yu-You; Zhou, Junhu; Lin, Richen
Highlights: Hydrothermal acid pretreatment strongly degraded algal bloom with tough cell walls. Increasing acid concentration in pretreatment led to increased crystallinity index. Hydrothermal acid (4% v/v) led to the highest H2 yield and CH4 yield. Hydrothermal acid (8% v/v) led to a decrease in CH4 yield due to Na + inhibition. Abstract: For the efficient utilization of algal biomass for gaseous biofuel production, hydrothermal acid pretreatment was employed in this study to hydrolyze algal bloom biomass harvested from Dianchi Lake in Yunnan Province of China. The hydrolyzed algal biomass was subjected to sequential dark hydrogen fermentation and anaerobic digestion to improve energy conversion efficiency (ECE). The results of X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy indicated that hydrothermal heating with increasing concentrations of sulfuric acid (H2 SO4 ; 0–8%) led to stronger damage to amorphous cellulose, which resulted in the increase in crystallinity index of cellulose. Hydrothermal heating with 4% H2 SO4 resulted in the maximum ECE of 55.7%, which yielded 37.33 mL H2 /g-total volatile solids (TVS) and 261.93 mL CH4 /g-TVS. However, the yields of hydrogen and methane were significantly reduced after hydrothermal pretreatment with 8% H2 SO4 which was most likely due to the substantial inhibitory effects on the bacteria and methanogens, caused by excess sodium ions introduced during pH adjustment process.